Menyelami Kearifan Kontekstual: Pemahaman Mendalam Terhadap Metode dan Teori Penafsiran Pemikiran Abdullah Saeed - Yessi Handriyani; Muhamad azhar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article aims to discuss Abdullah Saeed's thoughts on contextual interpretation of the Al-Qur'an. Abdullah Saeed considers it important to seek an open meaning of the Qur'an and it must be continued in accordance with current developments through contextual interpretation. The approach is based on the reality of the dominant literal (textual) interpretation of the Al-Qur'an, especially regarding ethical-legal verses. This type of research is a literature study with a qualitative approach. Data was obtained from studying Abdullah Saeed's thoughts and analyzed using the Al-Quran. The research results show that in terms of the theoretical basis, the contextual interpretation of the Al-Qur'an offered by Abdullah Saeed, among other things, can be traced through his ideas about the legal ethical interpretation of the Al-Qur'an, the concept of revelation and the textual-contextual approach.